Education in the Democratic Republic of Congo : Priorities and Options for Regeneration - World Bank (Washington, DC, 2012)
The main purpose of this report is to assist the Democratic Republic of Cong (DRC) to identify the priorities for education policy and present options in order to assist the government in developing an education strategy. This is necessary for preparing the government's Poverty Reduction Strategy Paper and a program of assistance for the education sector by external donors. This summary integrates the key findings and the recommendations presented in the Country Status Report on Education in the DRC. The Country Status Report is structured in six chapters covering the recent trends and current status of educational coverage, expenditures and financing at all levels of instruction in DRC, issues relating to quality in primary and secondary education and specific issues relating to higher education. It also presents the expenditure requirements under various policy options which can be used to begin a more detailed planning for the sector. The summary has three parts: (a) the main findings (b) the results of the financial simulations and (c) the key policy choices.